An Optimal Bidding Strategy of Power and Gas to Operate a Microgrid in Energy Market - Nahia Diez; Ivan Loya (Journal of Artificial Intelligence and System Modelling)
Microgrids could lower their costs in the day-ahead market through bidding in a smart distribution network. The bidding dilemma is difficult because there are many uncertainties. Despite the interdependence of gas and power prices on the balancing and day-ahead markets for a microgrid, the current study offers a two-step technique for the optimal power bids. In this instance, we looked into the interdependency of energy carriers, the impact of gas and power prices occurring simultaneously, and the impact of microgrid behavior on the power and gas bidding. The proposed network uses a two-step scenario to make bids in a microgrid. The distribution system operator receives hourly energy bids from the microgrid in the initial phase, regardless of uncertainty. The microgrid operator then assists in balancing the demand in the instantaneous market in the second phase while considering the established daily bids. By using GAMS and a scenario reduction technique, this problem is addressed as mixed-integer linear programming. The effectiveness of the suggested approach is demonstrated by numerical findings that compare scenarios for lowering the operating costs of ulti-carrier microgrids. According to the results, joint participation in the day-ahead and balancing markets reduced microgrid operation by about 2.5% compared to sole day-ahead/balancing market participation.